Axiomatic design applied to CRUD matrix in information systems - Cavique, Luís (2021)
In Information Systems (IS), the search for a good design is still a relevant issue. In IS, two sub-systems coexist, applications and data. To articulate these sub-systems, some authors opt for the CRUD matrix. Similarly, Axiomatic Design (AD) theory studies how functional requirements are related to design parameters using a design matrix. In this paper, the application sub-system corresponds to the functional requirements, the data sub-system to the design parameters, and the CRUD matrix to the design matrix. The goal of the CRUD matrix is to maintain the independence of its items to minimize the information content of the design. Similarly, AD uses the design matrix to define a good design. This work aims to develop a theory to create object-oriented elements based on the CRUD matrix aligned with the business strategy.